2019
DOI: 10.1016/j.jds.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pontic span and fiber reinforcement on fracture strength of multi-unit provisional fixed partial dentures

Abstract: Background/purposeClinically, PMMA resin is extensively used for fabricating provisional FPDs. However, fracture often occurs due to the unsatisfactory mechanical strength, especially within connectors of long-span provisional FPDs. The purpose of this study is to evaluate the fracture load of fiber-reinforced provisional FPDs with various pontic span lengths, and to identify the most suitable span length for fiber-reinforced long-span provisional FPDs.Materials and methodsFifty-six provisional FPDs with vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To improve the properties of PMMA materials, a variety of fibers have been added and extensively characterized ( Table 6 ). Several studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] have reported the improvement of various properties of fiber-reinforced PMMA. The characteristic reinforcement benefits are obtained due to the greater length of the fibers compared to the cross-sectional diameter.…”
Section: Modifications Of Pmmamentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the properties of PMMA materials, a variety of fibers have been added and extensively characterized ( Table 6 ). Several studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] have reported the improvement of various properties of fiber-reinforced PMMA. The characteristic reinforcement benefits are obtained due to the greater length of the fibers compared to the cross-sectional diameter.…”
Section: Modifications Of Pmmamentioning
confidence: 99%
“…Although there are a number of concerns associated with using PMMA, such as the fracture of dentures due to water sorption and poor impact and flexural strength, the ongoing research has introduced a variety of modifications to overcome and further improve its properties (such as its conductivity, water sorption, solubility, impact and flexural strengths). For example, several studies reported the improvement of PMMA materials while reinforced using a variety of fibers [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], nanoparticles [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and nanotubes [ 38 , 39 , 40 , 41 , 42 ]. Similarly, PMMA-based biocomposites with the addition of epoxy resins, polyamide, or butadiene styrene have been reported to improve the impact strength of PMMA [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to improve the mechanical performance of PMMA interim restorations by adding various filler particles such as fibers [27,28], NPs [29][30][31][32][33], and nanotubes [34][35][36]. The inclusion of inorganic nanofillers into PMMA changes the characteristics of the final product based on the size, shape, type, concentration, and filler to matrix interaction [33].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fractures are caused by water sorption, solubility, and aging because absorbed water acts as a plasticizer and decreases the strength of the resins. (3,28,29) Stress concentration during parafunctional or functional activities also leads to fractures particularly, in a connector of long-span transitional restorations. Moreover, minimum tooth reduction results in a thin restoration that is mostly exposed to fracture.…”
Section: (A) (B)mentioning
confidence: 99%
“…(3) The most common repair materials used are autopolymerized acrylic resins that have the ability to rebuild the defects, providing easy and fast manipulation but, the use of these properties than other fibers. (29,37) The most common fibers used in Commonly used materials for CAD/CAM interim fixed restorations include CAD/CAM polymethyl methacrylate (Figure 6) and composite resins . (6) Figure 6.…”
Section: -Improper External Contourmentioning
confidence: 99%